PENGGUNAAN CAMPUR KODE DALAM STATUS MEDIA FACEBOOK DI DESA CINERANG PADA BULAN FEBRUARI 2018 - Nuryani Nuryani; Robianti Robianti; Mimin Sahmini (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
Use mix code be trend by users various kinds of social media including social media facebook . With thereby increasingly many people started learn language foreigners . Use language foreigners are not free from influence mix code background by attitude speaker and language . Researchers choose 24 people in the village Cinerang on month February 2018 on social media Facebook many finding status or result data posts that use language foreigners . Research this aim for describe mix code on facebook status of 24 people in the village Cinerang on month February 2018 taken data from results observation . Method The research is descriptive qualitative . Research data in the form of facebook status of 24 people in the village Cinerang on month February 2018. Based on results research is known that mix code contained in facebook media status of 24 people in the village Cinerang on month The February 2018 in the form of words, phrases, baster, expression, and clause . Mix code the caused by attitude factor speaker and language and could knowing impact positive and negative from pengg unaan mix code in sosi al media facebook.